Effect of NPK Phonska Plus and Trichoderma Fertilizer Dosage on the Growth and Yield of Sweet Corn ( Zea Mays Saccharata Sturt ) - Sondari, Nunung; Amalia, Lia; Ulfah, Indriana; Perdi Ramadan, Harry (Jurnal Agrosci, 2024)
Sweet corn production in Indonesia has increased from 2015 by 19.83 million tons and increased to 23.16 million tons in 2016 (Ministry of Agriculture, 2020). Sweet corn production in Indonesia is low, with an average yield of around 8.31 t ha-1 (Garate, 2017). NPK fertilizer is one of the technologies in the agricultural business that facilitates farmers in applying plant nutrition because NPK fertilizer contains more than one type of nutrient. (Trichoderma sp is a microorganism or biological agent that can improve soil's physical, chemical, and biological properties. Trichoderma fungi make the soil structure loose, making it easier for roots to absorb nutrients, especially phosphate (P), and increase microbial activity. Trichoderma sp is a decomposer (decomposing species) and plant stimulator. The research method used is Randomized Group Design (RAK). The first factor is the application of NPK Phnska Plus fertilizer, and the second factor is the dose of Trichoderma sp. and the quadratic regression analysis test. There is an interaction effect between the dose of NPK fertilizer and the dose of Trichoderma on all parameters observed. NPK fertilizer dose of 6 grams/plant (P2) and Trichoderma dose of 20 grams/plant produced significant weight compared to other treatments. 45% of the variance of the treatment variable of NPK fertilizer dose and Trichoderma dose has not been able to explain the independent variable.